إصابات الصدر الحربية: دراسة سريرية وتحليل - رومية, دمر (Latakia University Journal -Medical Sciences Series, 2017)
إن الهدف الرئيس من هذه الدراسة هو تسليط الضوء وتحليل الأذيات الصدرية المختلفة أثناء النزاعات العسكرية.تمت دراسة وتحليل الملفات السريرية لـ (542) إصابة بأذيات صدرية أثناء فترة البحث.91.9% من المرضى كانوا ذكوراً، تراوحت أعمار المصابين بين (3 – 75) عاماً، 88.1% منهم كانوا في الأعمار بين (20 – 40) عاماً.71 إصابة إسعافية شديدة (13%) أدخلت مباشرة إلى غرفة العمليات، أما العدد الباقي من المرضى فقد أجريت لهم استقصاءات تشخيصية مختلفة، لعب التصوير الطبقي المحوري دوراً هاماً في تشخيص الأذيات الصدرية وقد أجري في 62.2% من الإصابات.92.8% من المرضى تعرضوا لأذيات صدر نافذة بسبب الطلق الناري مع أو بدون الشظايا والصواريخ. من بين الأذيات الحاصلة كان تكدم الرئة هو الغالب بنسبة 31.9% تلاه تدمي واسترواح الجنب بنسبة 29.15%، تمزق الرئة 14.39% 77 حالة (13.2%) من الجرحى أصيبوا بكسور أضلاع، 3 منهم (3.89%) شخص لديهم صدر سائب. تمزقات الحجاب حدثت لدى 6.45% من الجرحى ، الأذيات المشتركة شخصت لدى 61.07% من الحالات ، أغلبها 46.2% كانت أذيات في البطن ، 39.27% كانت أذيات رأس وعنق . The main aim of this study is to highlight and analyze the different thoracic injuries during the military conflicts. Medical records of 542 casualties with thoracic injuries were analyzed during study period.91.9% of the patients were male. The ages were ranging between 3 – 75 years، 88.1% of them were in the age between 20 – 40 years.71 top urgent casualties (13%) were directly admitted to op-theater، the remaining patients underwent different diagnostic procedures، CT-scan played an important role in the diagnosis of thoracic injuries and was performed in 62.2% of the casualties. 92.8% of the patients sustained penetrating chest injuries due to gunshots and / or missiles and shells. Of the injuries identified، the most prevalent injury was lung contusion، which occurred in 31.9% of casualties، traumatic haemo-and/or pneumothorax occurred in 29.15%، lung laceration in 14.39%، diaphragm injury in 6.45%. 77 patients (13.2%) sustained ribs fractures، 3 patients (3.89%) of them had a diagnosed flail chest injury. Combined injuries were reported to be 61.07% of all casualties.Most of them 46.2% were abdominal injuries، 39.27% were head and neck injuries.